Probing the Heart of Active Narrow-line Seyfert 1 Galaxies with VERA Wideband Polarimetry - Mieko Takamura; Kazuhiro Hada; Mareki Honma; Tomoaki Oyama; Aya Yamauchi; Syunsaku Suzuki; Yoshiaki Hagiwara; Monica Orienti; Filippo D’Ammando; Jongho Park; Minchul Kam; Akihiro Doi (The Astrophysical Journal, 2023)
We explored the parsec-scale nuclear regions of a sample of radio-loud narrow-line Seyfert 1 galaxies (NLSy1s) using the VLBI Exploration of Radio Astrometry wideband (at a recording rate of 16 Gbps) polarimetry at 22 and 43 GHz. Our targets include 1H 0323+342, SBS 0846+513, PMN J0948+0022, 1219+044, PKS 1502+036, and TXS 2116-077, which are all known to exhibit γ -ray emission indicative of possessing highly beamed jets similar to blazars. For the first time, we unambiguously detected Faraday rotation toward the parsec-scale radio core of NLSy1s, with a median observed core rotation measure (RM) of 2.7 × 10 ^3 rad m ^−2 (or 6.3 × 10 ^3 rad m ^−2 for redshift-corrected). This level of RM magnitude is significantly larger than those seen in the core of BL Lacertae objects (BLOs; a dominant subclass of blazars), suggesting that the nuclear environment of NLSy1s is more gas-rich than that in BLOs. Interestingly, the observed parsec-scale polarimetric properties of NLSy1s (low core fractional polarization, large core RM and jet–EVPA misalignment) are rather similar to those of flat-spectrum radio quasars (FSRQs). Our results are in accordance with the scenario that NLSy1s are in an early stage of active galactic nucleus evolution with their central black hole masses being smaller than those of more evolved FSRQs.